The Influence of Powerpoint-Based Interactive Teaching Media on Motivation and Learning Outcomes of Social Studies Learning in Class V of SDN Sadeng 03 - Tia, Tia; Tri Astuti; Adinda Assyfa Nurdina; Mezaluna Kharismatika Deazzuri; Farida Lulu Asmara; Jazilatun Nikmah (Jurnal Riset Ilmu Pendidikan, 2025)
Social studies learning using interactive Powerpoint-based teaching media is one form of technology integration in education that is relevant to the development of the times. This media utilizes visual displays and animations to attract students' attention and facilitate understanding of the material. This study uses a quantitative method with an ex-post facto approach conducted in class V of SD Negeri Sadeng 03. Data collection techniques in this study were interviews with homeroom teachers, documentation, distribution of motivation questionnaires, and student learning outcome data. This study aims to determine the effect of the use of Powerpoint media on learning motivation and student learning achievement in social studies. The results showed that all students had high learning motivation with 55.2% in the "Strongly Agree" category and 44.8% in the "Agree" category, without any negative responses. Before the application of Powerpoint learning media, there were still 10 students who had not reached the KKTP, but after that there was an increase in learning outcomes by an average of around 10%. Interactive learning media also strengthens students' interests and understanding. This study confirms the existence of a mutually reinforcing relationship between learning motivation and learning outcomes, where learning success is influenced by the synergy between student motivation and the effectiveness of the methods used.